O campo do ensino médio público brasileiro através das práticas de sociabilidade em rede: análise das páginas de Facebook das escolas estaduais - Oliveira, Luis Felipe Rosa de (2019)
Starting from the motivation to expand the ways of appropriation of the digital space by the social sciences and communication, the dissertation research proposed here, presents an applied approach of scientific investigation of the digital environment. Using the conceptual methodological repertoire of Pierre Bourdieu, and updating it from the relational context of the contemporary web and the perception of the digital objects, it is proposed the study of the identification and description of network sociability practices in the Facebook pages of the brazilian state public schools high school. Applying the analytical techniques of contextual description of data, social networks analysis, domains and links analysis and correlation analysis, it was possible to outline the social context of the school field present in Facebook, as well as identified practices with specific characteristics of the network, as the practice of relevance, of symbolic diffusion and articulation of power, constituting some components of the network sociability practices of schools.